El Sistema Bethesda 2001 The 2001 Bethesda System - Christine Bergeron (Instituto Nacional de Salud Pública, 2003)
The Bethesda system is a system of terminology for reporting the results of cervical cytology. It was developed in 1988, and is now widely used in the United States. This system was updated in April 2001. The most important modifications are the following: a) elimination of the category "satisfactory but limited by", b) the reintegration of benign modifications in the normal category, c) "atypical squamous cells of undetermined significance" is now named "atypical squamous cells" and subdivided into "atypical squamous cells of undetermined significance" and "cannot exclude high grade squamous intraepithelial lesion"; and d) endocervical adenocarcinoma in situ which is now a separate entity. Low grade squamous intraepithelial lesions and high grade squamous intraepithelial cells remain unchanged. Recommendations have been proposed concerning automated review and ancillary testing. El Sistema Bethesda es un sistema de terminología para informar los resultados de citología cervical. Se inició en 1988 y en la actualidad se usa en todos los Estados Unidos de América. Este sistema se actualizó en abril de 2001. Las modificaciones más importantes son las siguientes: a) eliminación de la categoría "satisfactorio pero limitado por", b) se reintegraron las modificaciones benignas en la categoría normal, c) la categoría "células escamosas atípicas de significado indeterminado" ahora se denomina "células escamosas atípicas", y se subdivide en "células escamosas atípicas de significado indeterminado" y "no se puede excluir una lesión escamosa de alto grado", y d) adenocarcinoma endocervical in situ, que ahora es una entidad separada. Las lesiones escamosas intraepiteliales de bajo y alto grado quedan sin cambios. Se proponen recomendaciones relacionadas con el uso de la revisión automatizada y la utilización de pruebas auxiliares.